2011
DOI: 10.1002/gj.1312
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical characterization and petrogenesis of Proterozoic Khairagarh volcanics: implication for Precambrian crustal evolution

Abstract: The Khairagarh volcano-sedimentary sequence is exposed along the Kotri-Dongargarh Belt towards the north-eastern part of the Bastar Craton. This sequence is exposed south of the Central Indian Shear (CIS) and east of the Sakoli Group rocks. The Khairagarh volcanic sequence is represented by low-Ti, intermediate-Ti and high-Ti basalt-basaltic andesite series that probably represent varying degrees of partial melting of an enriched mantle source, thus they appear to be consanguineous. These rocks are associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 51 publications
1
18
0
Order By: Relevance
“…SiO2 ranges from 48-54 wt%, Fe2O3 from 8-16 wt%, MgO shows a little wide range from 3-15 wt% and Al2O3 from 11-15 wt%. Based on the Ti-content of the studied Basalts, these are subdivided into two groups; low-Ti basalts having Ti < 0.9 wt% and relatively high-Ti basalts having Ti > 0.9 wt% [1] [10] [13]. The plot of compiled data are showing the composition of basalt to basaltic-andesite in composition, lying in the sub-alkaline field in the total alkalis versus silica (TAS) diagram (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SiO2 ranges from 48-54 wt%, Fe2O3 from 8-16 wt%, MgO shows a little wide range from 3-15 wt% and Al2O3 from 11-15 wt%. Based on the Ti-content of the studied Basalts, these are subdivided into two groups; low-Ti basalts having Ti < 0.9 wt% and relatively high-Ti basalts having Ti > 0.9 wt% [1] [10] [13]. The plot of compiled data are showing the composition of basalt to basaltic-andesite in composition, lying in the sub-alkaline field in the total alkalis versus silica (TAS) diagram (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Asthana et al [3] categorised the Pitepani suits as high-Mg, low-Ti suits and low-Mg, high-Ti suits. Whereas Sitagota basalts show a wider range in concentration of these elements and can be grouped into high-Ti basalts and low-Ti basalts [1][10] [13].…”
Section: Resultsmentioning
confidence: 99%
“…Neogi et al (1996) also ascribed that these lavas were erupted in a continental rift environment. Asthana et al (1996), and Longjam and Ahmad (2012) suggested that the Khairagarh mafic volcanics are similar to island-arc magmas and have been developed under Andean-type subduction zone environments for the high-Mg andesites and Andean-type back-arc rifting for the basalt-basaltic andesites. Adjacent to the Khairagarh Group, Sakoli bimodal volcanics are well exposed and constitute meta-basalts, rhyolite, tuffs, epiclastic rocks with metapelites, quartzites, arkose, conglomerates, and iron formations.…”
Section: Regional Geological Settingmentioning
confidence: 99%
“…The Khairagarh Group is exposed in the south‐western margin of the Chhattisgarh Basin comprising low‐Ti and high‐Ti basalts (Asthana et al ., ). The depleted mantle model ages (Sm–Nd isotopic analysis) of these volcanics ranges from 2984 to 2489 Ma (Longjam and Ahmad, ). The rhyolites in the Nandagaon Group have been included under the Bhijili rhyolites, composed of thick stacks of felsic volcanics, un conformably overlying the gneissic rocks of the older Amgaon Group with a thickness of 4500 m (Sarkar, ).…”
Section: Regional Geological Settingmentioning
confidence: 99%
“…The subsequent three articles deal with the different geological aspects of the Bastar Craton. Longjam and Ahmad () investigate the Khairagarh volcanics, the magmas of which were extracted from an enriched mantle at 2.9–2.5 Ga, and accreted to the Columbia supercontinent along an Andean‐type subduction zone within a back‐arc setting. Mid‐Archaean to Palaeoproterozoic mafic dyke swarms in the Bastar Craton are investigated by Srivastava and Gautam (), who correlate their diversities and geochemical signatures to different degrees of partial melting in the mantle and suggest the involvement of plumes.…”
mentioning
confidence: 99%